Avaliação do uso de linezolida: revisão sistemática e estudo de custo-minimização - Taguti, Érika (2014)
The aims of this research were update systematic reviews available about partial and complete economic studies of linezolid and estimate differential cost between intravenous and oral administration with hypothetical linezolid switch therapy (intravenous to oral or nasogastric tube). A systematic review was conducted using the terms "clinical outcomes", "analysis cost", "economic outcomes" and "pharmacoeconomic studies" and "linezolid" in the databases Cochrane, IPA, Medline and Scopus, associated with manual search. It was also conducted a cost-minimization analysis among hospitalized patients who used oral and/or intravenous linezolid forms between August, 2009 and August, 2013 in a public hospital in southern Brazil. The research was presented in three different papers. For systematic review were found 1352 articles, of which 24 fulfilled inclusion criteria for the systematic review of partial economic studies and 43 for systematic review of complete economic evaluations. In general, linezolid showed better clinical and economic outcomes compared to antimicrobials such as vancomycin, daptomycin, teicoplanin, particularly in cases of pneumonia patients, infections of skin and soft tissues, infections of methicillin-resistant Staphylococcus aureus, for systematic review of partil and complete economic evaluations, due to the possibility switch therapy. In study of cost-minimization were evaluated records of 152 patients, 103 (67.8%) were treated with linezolid exclusively intravenous route and in 33 (31.7%) opportunities could have been the exchange to oral form administration of antimicrobial. The total cost per patient (mean) after changing from intravenous to oral administration was significantly lower than the real cost paid per patient (mean) (p<0.001). The cost savings associated with switching to oral linezolid administration would be US$14,328.32 over four years.